Can advance care planning (ACP) improve patients' journey with advanced dementia and their families? A 1-year follow-up study - Kuen Lam; Faye Chan; Derek Lai; Connie Tong; Christopher Lum; Jean Woo (Clinical Medicine)
Introduction: With the recent legalisation of Advance Medical Directive (AMD) in Hong Kong, public awareness of advance care planning (ACP) has significantly increased. Despite this progress, significant challenges remain in integrating ACP into the local Chinese culture context and implementing it effectively within the busy public healthcare system.The study aimed to explore the journey of patients with advanced dementia and their families after they had been equipped with knowledge about ACP. By following their experience over 1 year, we seek to gain insights into how ACP can be better utilised to improve the quality of clinical services and provide enhanced support for family caregivers of older adults with advanced dementia. Methods: Patients with advanced dementia admitted to the medical wards of a convalescent hospital were invited to participate in interactive sharing sessions with their family members. During these sessions, the concept of ACP and life-sustaining treatments (LSTs) were explained. For patients who expressed interest in completing ACP documents, follow-up appointments were arranged at the medical clinic to facilitate the signing process.One year after attending the sharing sessions, all participants were invited to take part in a telephone interview study. The interviews aimed to explore their experiences and perceptions regarding how knowledge of ACP influenced the patients’ journey throughout the course of their disease. The interviews were transcribed verbatim and analysed using a thematic content analysis framework. Results: From March 2021 to October 2024, 31 sharing sessions were conducted, reaching 178 family members of 129 patients. Six patients completed the ACP documents. The overall feedback was positive among the 131 participants who responded to the evaluation surveys for the sharing sessions. After attending the sessions, participants indicated a significant improvement in their knowledge of ACP, AMD and LST.A 1-year follow-up interview was conducted with 23 participants. They shared that attending the ACP sharing sessions helped family members reflect more deeply and engage in meaningful conversations with patients. Even in cases where ACP was not formally completed (ie, no documents were signed), family members reported a better understanding of the patient’s preferences. Additionally, family caregivers felt more emotionally prepared for the patients’ passing after engaging in ACP discussions, which helped minimise unresolved concerns or ‘unfinished business’.However, participants also highlighted challenges. Initiating conversations about ACP was difficult, because local Chinese culture often avoids the topic. Furthermore, participants expressed disappointment that their expectations for more follow-up care after ACP discussions were unmet. They emphasised the strong need for additional support at the community level – for both the medical and caregiving needs of patients with advanced dementia – to ensure that the wishes outlined in the ACP could be fulfilled. Conclusion: This study demonstrates that ACP can improve the journey of patients with advanced dementia and their families by fostering meaningful conversations, clarifying patient preferences, and preparing caregivers for end-of-life transitions. However, cultural barriers and insufficient follow-up care remain significant challenges. Culturally sensitive strategies, enhanced community-level support, and empowering caregivers with knowledge of community resources are essential to fully realise the benefits of ACP and improve care for patients and their families.